Determining the Role of Pedestrian-Orientation, Concerning the Public Places: Improvement of Urban Social Capital Quality - Mohammad Moayedi; Reza Kheyroddin; Ismail Shieh (Civil Engineering Journal, 2019)
Studying the status of urban social capital indicates that it is declining in contemporary cities. The experts in the field of social science have seriously warned on the consequences of this decline, by examining the components of social capital which is the result of forming norms of collective life and social interaction. In this regard, urbanization knowledge seeks to strengthen social capital through targeted interventions and efforts to improve the quality of urban life. Social interactions are significantly important factors contributing to the social capital and one of the most effective ways of realizing social interactions is making and developing of "public urban places". Regarding the previous studies which show that public places are created for people's presence and social mobility, this study seeks the ways for strengthening social capital by interventions in public places and increasing their quality by determining the role of urban spaces in improving the status of social capital. For a better study of the subject, using a desk research method, field observation and scrolling through a questionnaire, the market pedestrian located in the central area of Tehran was studied. The collected data were analyzed by SPSS software and the results showed that interventions with the aim of pedestrianizing and attempts to make a high quality place increase presence of people and cause a high tendency to establish social interactions.in fact pedestrian-orientation of urban areas has facilitated face-to-face and collective communication by influencing the social trust and solidarity, also it has helped with strengthening the tendency to participate and cooperate. Hence, adoption of the pedestrian-orientation policy and efforts to improve the quality of public places, have enhanced the social capital of city.